Entrepreneurial Potential and Potential Entrepreneurs - Krueger, Norris F.; Brazeal, Deborah V. (Entrepreneurship Theory and Practice, 1994)
Before there can be entrepreneurship there must be the potential for entrepreneurship, whether in a community seeking to develop or in a large organization seeking to innovate. Entrepreneurial potential, however, requires potential entrepreneurs. This paper discusses antecedents of such potential and proposes a model based on Shapero's (1982) model of the entrepreneurial event. We then discuss this model in light of supporting evidence from two different perspectives, corporate venturing and enterprise development.